Development, Implementation, and Outcomes of a Delirium Protocol in the Surgical Trauma Intensive Care Unit. (January 2017) - Sullinger, Danine; Gilmer, Alexander; Jurado, Lesly; Zimmerman, Lisa Hall; Steelman, Joshua; Gallagher, Ann; Dupre, Tiffany; Acquista, Elizabeth
Background: Delirium in the critically ill is associated with increased mortality, length of stay (LOS), and prolonged cognitive dysfunction. Existing guidelines provide no recommendation for use of combination nonpharmacological and pharmacological prevention protocols or use of antipsychotic medications for the prevention or treatment of delirium.Objective: This study evaluated the impact of implementing a delirium treatment protocol on the number of delirium-free days experienced by acutely delirious patients in the surgical trauma intensive care unit (STICU).Methods: This retrospective, institutional review board–approved, pre-implementation (PRE) versus post-implementation (POST) cohort evaluated delirious patients admitted to the STICU. Patients were evaluated based on the duration of delirium. Secondary end points included ICU LOS, amount of atypical and typical antipsychotic medication used, amount of analgesia and sedation used, and adverse drug events associated with antipsychotics.Results: Of the 593 evaluated, 89 patients were included (38 PRE vs 51 POST). Implementation of a delirium protocol reduced the number of delirious days, 8.2 ± 5.7 days PRE versus 4.5 ± 4.4 days POST; P = 0.001. ICU LOS in surviving patients and use of concomitant medications, intravenous morphine equivalents, and propofol were significantly reduced in the POST group.Conclusion: The implementation of a delirium protocol with nonpharmacological and pharmacological interventions had an impact on STICU patients experiencing acute delirium by significantly increasing delirium-free days and reducing the ICU LOS, in addition to decreased administration of concomitant medications.